The Spread of Snow Avalanches at Transport Junctions in the Mountainous Regions of Georgia - Gorgidjanidze, Sophio; Beglarashvili, Nazibrola; Pipia, Mikheil; Kobakhidze, Natela (European journal of sustainable development, 2023)
The snow avalanche has an insidious character, it can be repeated once in 100-200 years and cause great harm to the population of the mountainous region. There are many examples of damage caused by avalanches. In the 20th century, several thousand soldiers were died by avalanches in the Alps during the First World War, on the Austrian-Italian front. There are many examples of them not only in the Alps but also in the mountainous regions of Georgia. Frequently, snow avalanches block important transportation routes that connect people and countries. In general, 56% of the territory of Georgia is covered with avalanche-prone slopes. Based on existing examples, it is important to record and study them, because snow avalanches are characterized by repetition. Examples of this are Svaneti, Racha and Mtianeti (regions of Georgia). It is worth noting the Mleta-Kazbegi section road (Georgia's military road), where there is a danger of avalanches every year, which is the subject of our research. The highway of Georgia is a transport hub of international importance. Therefore, observation of avalanches, study and carrying out various measures is a necessary prerequisite in order to avoid damage caused by avalanches. Keywords: Mountainous regions, avalanche danger, climate, natural phenomena, transport infrastructure